2012
DOI: 10.5140/jass.2012.29.3.295
|View full text |Cite
|
Sign up to set email alerts
|

Radiosonde Sensors Bias in Precipitable Water Vapor From Comparisons With Global Positioning System Measurements

Abstract: In this study, we compared the precipitable water vapor (PWV) data derived from the radiosonde observation data at Sokcho Observatory and the PWV data at Sokcho Global Positioning System (GPS) Observatory provided by Korea Astronomy and Space Science Institute, for the years of 2006, 2008, 2010, and analyzed the radiosonde seasonal, diurnal bias according to radiosonde sensor types. In the scatter diagram of the daytime and nighttime radiosonde PWV data and the GPS PWV data, dry bias was found in the daytime r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…From our results, we infer that the lower differences at 0900 LT are due to a dry bias (for all intervals of the IWV estimates) in radiosonde during daylight time as observed comparable underestimation order of magnitude by [65,66] (see additionally [14,[67][68][69][70][71][72]).…”
Section: Modis-versus Gnss-derived Iwvsupporting
confidence: 69%
“…From our results, we infer that the lower differences at 0900 LT are due to a dry bias (for all intervals of the IWV estimates) in radiosonde during daylight time as observed comparable underestimation order of magnitude by [65,66] (see additionally [14,[67][68][69][70][71][72]).…”
Section: Modis-versus Gnss-derived Iwvsupporting
confidence: 69%
“…As consequence of the inhomogeneity of altitude and meteorological conditions of the collocated stations used in this work, we observed that the atmosphere above RADS (located in an island) were about 2.3 mm wetter than above RDJN (located on a urban small hill) and 1.2 mm wetter than above RIOD (located in a urban valley) at 21:00 LT. The IWV differences between RDJN and RIOD remained consistently around 1.1 mm in the daytime, while IWV RADS estimates would be 1.4 mm (or 3.7%) lower than it was expected in the absence of bias, as observed comparable underestimation order of magnitude by Sapucci et al [65] and Turner et al [66] (see references [15,[67][68][69][70][71][72]). However, we cannot discard bias in GNSS IWV due to some other influences that were not computed in this work, and the different meteorological conditions in the sites.…”
Section: Discussionmentioning
confidence: 61%
“…Considering the noise level in the RT-PPP ZTD estimates, we argue that the statistics computed over the one month give a good indication of the quality (precision and the stability of biases) of the estimates. However, we acknowledge that the seasonality of the IWV may have a small influence on the comparison between the GNSSderived and RS-based ZTD (Park et al 2012), which cannot be seen using the one month period.…”
Section: Real-time Data and Productsmentioning
confidence: 95%